2011
DOI: 10.1007/s00429-011-0302-4
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between hippocampal microstructure, metabolism, and function in early Alzheimer’s disease

Abstract: Abnormal microstructural integrity and glucose metabolism of the hippocampus are common in subjects with Alzheimer's disease (AD) that typically manifest as episodic memory impairment. The above-tissue alterations can be captured in vivo using diffusion tensor imaging (DTI) and positron emission tomography with [18F]fluorodeoxyglucose (FDG-PET). Here, we explored relationships between the above neuroimaging and cognitive markers of early AD-specific hippocampal damage. Twenty patients with early AD (MMSE 25.7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…In multiple sclerosis patient who exhibit demyelinated axons also shown remote effects on CMRglc with significant glucose metabolic depression in the thalamus and cerebellum (Derache et al, 2006). This type of denervation induced CMRglc decrease has also been reported in Alzhiemer's disease (Yakushev et al, 2011). Damage to axons and or decreases in synaptic connectivity can directly affect cerebral activity levels, CMRglc and behavioral outcome (Browne et al, 2001).…”
Section: What Causes Cmrglc Depression?mentioning
confidence: 84%
“…In multiple sclerosis patient who exhibit demyelinated axons also shown remote effects on CMRglc with significant glucose metabolic depression in the thalamus and cerebellum (Derache et al, 2006). This type of denervation induced CMRglc decrease has also been reported in Alzhiemer's disease (Yakushev et al, 2011). Damage to axons and or decreases in synaptic connectivity can directly affect cerebral activity levels, CMRglc and behavioral outcome (Browne et al, 2001).…”
Section: What Causes Cmrglc Depression?mentioning
confidence: 84%
“…Our study could not find significant difference in FA maps between groups. Previous reports of FA abnormalities in mild AD have predominantly employed Region Of Interest (ROI) based approaches, as opposed to our whole‐brain voxel‐wise approach (Yakushev et al ., ; Nowrangi et al ., ; Tighe et al ., ). To the best of our knowledge, there has been only one study by Bosch et al ., reporting reduction in FA among mild AD using voxel wise whole brain white matter tract comparisons; however, the results reported in this study were unadjusted for age and gender variations (Bosch et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Diffusion weighted imaging (DWI) with apparent diffusion coefficient (ADC) mapping and diffusion tensor imaging (DTI) has been used to investigate the white matter changes in areas such as the temporal lobe, hippocampus and corpus callosum (Ramani et al, 2006; Small et al, 2008; Stebbins and Murphy, 2009). In particular, DTI is capable of assessing microstructural and connective changes in the hippocampus and its related structures, arising from neuronal loss and axonal degeneration (Yakushev et al, 2011a,b; Hattori et al, 2012). Alternatively, magnetization transfer imaging (MTI) is able to detect structural damage as a reduction in the magnetization transfer rate (MTR) reflects decreased tissue homogeneity from pathological changes such as neuronal loss and gliosis in gray matter, and demyelination and axonal loss in white matter (Glodzik-Sobanska et al, 2005; Ramani et al, 2006).…”
Section: Neuroimaging In Alzheimer's Diseasementioning
confidence: 99%
“…Axonal degeneration and white matter changes that occur secondary to neuronal loss can be investigated with DTI. Yukashev and colleagues demonstrated that both macroscopic changes shown by volumetric analysis and microstructural changes revealed by DTI lead to metabolic changes in the posterior cingulate cortex (Yakushev et al, 2011a,b). Hattori et al (2012) utilized DTI to analyse the fornix, which contains efferent fibers from the hippocampus, in AD patients and patients with normal pressure hydrocephalus (NPH) which is another cause of progressive dementia.…”
Section: Current Status Of Neuroimaging Biomarkers In Alzheimer's Dismentioning
confidence: 99%